A highly stereoselective and efficient synthesis of enantiomerically pure sitagliptin. Issue 1 (15th January 2017) - Kang, Sung Kwon; Cho, Gyeong Hi; Leem, Hyung Joon; Soh, Bong Kwan; Sim, Jaehoon; Suh, Young-Ger
Graphical abstract: Abstract: A highly stereoselective and efficient synthesis of sitagliptin1 consisting of a chiral β-amino acid unit has been achieved through 6 steps from commercially available 2, 4, 5-trifluorobenzaldehyde4 . The chiral antidiabetic drug was obtained with almost perfect enantiomeric purity (>99.9% ee) in 40.9% overall yield. The key feature of the synthesis is the addition of a malonate enolate to a chiral sulfinylimine in more than 99:1 dr. Our synthetic procedure proved to be highly efficient, economical, and sustainable. Abstract : 7-[(3 R )-3-Amino-1-oxo-4-(2, 4, 5-trifluorophenyl)butyl]-5, 6, 7, 8-tetrahydro-[3-(trifluoromethyl)-1, 2, 4-triazolo[4, 3-a]pyrazine (1 ): C16 H15 F6 N5 O ee % = 100% Absolute configuration: ( R ) [ α ]D 20 −22.72 ( c  1, CHCl3 )